2019
DOI: 10.1136/jnnp-2019-321523
|View full text |Cite
|
Sign up to set email alerts
|

Clinically stable disease is associated with a lower risk of both income loss and disability pension for patients with multiple sclerosis

Abstract: ObjectiveTo assess the risk of losing income from salaries and risk disability pension for multiple sclerosis patients with a clinically stable disease course 3 years after the start of disease-modifying therapy (DMT).MethodsData from the Danish Multiple Sclerosis Registry were linked to other Danish nationwide population-based databases. We included patients who started treatment with a DMT between 2001 and 2014. Patients were categorised into a clinically stable group (No Evidence of Disease Activity (NEDA-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Treatment effectiveness of Interferon‐β is not different in women and men (Magyari et al, 2014). Clinically stable disease is associated with a lower risk of both income loss and disability pension for patients with multiple sclerosis (Chalmer et al, 2020). Treatment escalation leads to fewer relapses compared with lateral switching to another moderately effective therapy (Chalmer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment effectiveness of Interferon‐β is not different in women and men (Magyari et al, 2014). Clinically stable disease is associated with a lower risk of both income loss and disability pension for patients with multiple sclerosis (Chalmer et al, 2020). Treatment escalation leads to fewer relapses compared with lateral switching to another moderately effective therapy (Chalmer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…• Clinically stable disease is associated with a lower risk of both income loss and disability pension for patients with multiple sclerosis (Chalmer et al, 2020).…”
Section: Ms Cohort Observational Studiesmentioning
confidence: 99%
“…[14,15] A recent study of patients in Denmark demonstrated that a clinically stable disease course was associated with a reduced risk of losing income from salaries and disability pension compared with those that did not have a clinically stable disease course. [22] Studies in other therapeutic areas showed that simpler and less frequent dosing led to greater adherence than more frequent administration. [23][24][25] The current study is unique in that it provided primary data on the indirect costs of MS, which are not readily available and are not commonly evaluated, particularly in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Health care services should consider the benefits of an agile infusion service that supports continued employment and the psychological impact of nonemployment. 15,16 Thirty-six percent of the employed or studying respondents preferred infusion times after noon, in contrast to only 17% of those not working or studying. However, working and studying respondents are slightly less likely to prefer/consider home infusions.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%